A magnum opus - discussed: Faith, freedom, and family: new studies in law and religion. By John Witte, Jr. Edited by Norman Doe and Gary S. Hauk. Tübingen: Mohr Siebeck, 2021. Pp. 791. €99.00 (paper); €99.00 (digital). ISBN: 9783161608766 : book review symposium - Welker, Michael (Journal of law and religion, 2023)
Over the first two decades of the twenty-first century, John Witte, Jr. has not only carefully documented but also creatively promoted in many ways three very important developments: (1) the almost revolutionary worldwide reawakening of cooperation in the fields of law and religion after the termination of their long, fruitful history of cooperation in the mid-1800s; (2) the efforts to strengthen a justice-oriented legal culture in democratic societies and the legal, academic, and political appreciation of human rights (also in disputes with human rights skeptics); and (3) the reconciliation of traditional values and new needs for freedom in the ethos and law of marriage and family.